IPO Long-Term Performance: Evidence from Indonesia Stock Exchange 2019-2020 - Fuadi, Ali Akbar; Pasaribu, Pananda (EQUITY, 2024)
Initial Public Offering (IPO) is one of the most anticipated events in in the Indonesia Stock Exchange (IDX). The number of companies going public has increased significantly in the last few years. However, some newly listed stocks do not perform well after they are listed.  This paper will examine whether information stated in the prospectus documents have a significant influence on the long run IPO stock price between 2019-2020. The information includes financial ratios, intention of proceeds, dividend policy, and underwriter reputation.  This study uses  an event  study approach, in which 106 IPO events, to analyse stock performance three years after the IPO. The dependent variable is buy and hold abnormal return (BHAR). The result shows that DER ratio and intention use of proceeds for debt repayment are significant to influence BHAR with a negative relationship. Moreover, the underwriter reputation and underpricing level are insignificant to affect BHAR. The study concluded that long term performance of newly listed firm is influenced by the leverage level.   Keywords: Initial Public Offering (IPO), Stock Performance, Indonesia Stock Exchange (IDX)